P1341FACTORS AFFECTING THE ATTAINMENT OF ADEQUATE BLOOD FLOW OF ARTERIOVENOUS FISTULA FOR HEMODIALYSIS. (6th June 2020) - Gjorgjievski, Nikola; Dzekova-Vidimliski, Pavlina; Stojanoska, Ana; Gjorgievska, Julija; Dejanov, Petar; SELIM, GJULSEN; Nikolov, Igor; Rambabova Bushljetikj, Irena; Petronijevik, Zvezdana; Muharremi, Shqelkim; Spasovski, Goce; Ivanovski, Ninoslav; et al.
Abstract: Background and Aims: An arteriovenous fistula (AVF) remains the best choice of vascular access (VA) for hemodialysis (HD). The aim of our study was determination of factors associated with achieved adequate blood flow (BF) of AVF during 4-th week after creation Method: : Created AVF in 63 patients with chronic kidney disease (CKD) stage 4, 5 and 5-HD were analyzed in the prospective single center study, from January 2019 to October 2019. Preoperative mapping of blood vessels by Doppler ultrasound (DUS) on the forearm was performed in all patients. All patients were undergoing surgical creation of new forearm AVF (radio-cephalic) by one doctor. The DUS was used for measuring the diameter size of artery radialis, artery brachialis and vein cephalica before creation of AVF and again on 1-st day, 2-nd and 4-th week after AVF creation. In addition the BF of AVF was also measured by DUS on 1-st day, 2-nd and 4-th week after AVF creation. The adequate BF of AVF for hemodialysis treatment was defined as ≥ 600 ml/min. Patient gender and age, hemodialysis vintage, diameter size of artery radialis, artery brachialis and vein cephalica before creation of AVF were analyzed as factors that were affecting the achieved BF of AVF during 4-th week after creation. Results: : The average age of patients was 61.31 ± 12.9 years. From all patients, 60.31% (38/63) were men. The adequate BF of AVF (≥600 ml/min) during 4-th week after creation was achieved in 43.54% (27/63) of created AVFs. The blood flow of AVF measured in male gender was significantly higher compared to the blood flow of AVF measured in female gender (576.03 ml/min vs 375.12 ml/min, p=0.004). The age of the patients and hemodialysis vintage were not significantly associated with achieved adequate BF of AVF during 4-th week after creation of AVF. The adequate BF of AVF was achieved in blood vessels with bigger diameter size. The diameter size of the blood vessels with achieved adequate BF was significantly higher compared to the diameter size of the blood vessels without adequate BF (artery radialis : 2.45 mm vs 2.03 mm, p=0.000; artery brachialis: 4.78 mm vs 4.06 mm, p=0.001 and vein cephalica: 3.12 mm vs 2.83 mm, p=0.018). Conclusion: The gender and the diameter size of artery radialis, artery brachialis and vein cephalica before creation of AVF were significantly associated with achieved adequate BF of AVF (≥600 ml/min) during 4-th week after creation of AVF.